Edukasi Pasien Tentang Puasa Pra-Operasi Dan Dampaknya Terhadap Keselamatan Anestesi - Rahayu Setyaningsih (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Preoperative fasting is an important procedure in preparing patients before surgical procedures involving anesthesia. Patient noncompliance with fasting rules can increase the risk of aspiration, respiratory disorders, and other anesthesia complications. However, many patients still do not understand the purpose and rules of preoperative fasting correctly. This community service activity aimed to increase patient knowledge and compliance regarding preoperative fasting and its impact on anesthesia safety. The methods used included health education through counseling, leaflets, interactive discussions, and pre-test and post-test evaluations. The results of the activity showed a significant increase in patient knowledge from 45% to 85% after education. In addition, most patients demonstrated a better understanding of the timing and types of food that can be consumed before surgery. This education is expected to improve patient safety and reduce the risk of anesthesia complications.